Media Management of the National Amil Zakat Agency in Attracting Muzaki's Interest in Labuhanbatu Regency - Muhammad Akbar Jayadi; Hasnun Jauhari Ritonga (Journal of Research in Business, Economics, and Education, 2023)
This study aims to determine the media management of the National Amil Zakat Agency in attracting muzakis in Labuhanbatu Regency. This study uses a descriptive method with a qualitative approach. This research was conducted in the field (field research). This study uses primary data sources and secondary data sources. In data collection techniques, this study used semi-structured interviews and observations, then the data obtained was analyzed through the reduction stage, presented then concluded, the aim is to make systematic research so that it makes it easier for readers to understand the intent and purpose of this research. The results of this study indicate that the media management of the National Amil Zakat Agency in attracting muzakis in Labuhanbatu Regency is by taking strategic steps through the planning, organizing, implementing and monitoring stages which are then connected to the communication activities of the National Amil Zakat Agency through the media. In alleviating poverty, the involvement of muzaki is needed, this is a step to help each other. In this activity, a series of stimuli is needed to influence muzaki so that their interest in zakat increases, the communication activities carried out by the National Amil Zakat Agency are based on the suitability between the message and the response. As for ongoing communication efforts to stimulate muzaki, the National Amil Zakat Agency uses media in the form of Instagram and the Baznaslabuhanbatu.go.id website.